The Economy of West Bank and Gaza : Recent Experience, Prospects, and Challenges to Private Sector Development - Barnett, Steven (International Monetary Fund, 1998)
The economy of the West Bank and Gaza Strip faces a difficult external environment in 1997. This paper, by Steven Barnett, Nur Calika, Dale Chua, Oussama Kanaan, and Milan Zavadijil, presents an assessment of the recent experience of the Palestinian economy and examines prospects for 1998 and beyond.